PEMBELAJARAN INSTRUKSIONAL TERPROGRAM DALAM PENINGKATAN EFEKTIVITAS PEMBELAJARAN GAMBAR TEKNIK - Subiyono Subiyono (Jurnal Cakrawala Pendidikan, 2009)
AbstractThis study aimed to find empirical evidence that in Technical Drawing studentstaught by the programmed instruction model attained higher achievement thanthose taught by the conventional teaching model. This study was a quasiexperimentalstudy. The research subjects were students of the Department ofMechanical Engineering, the Faculty of Engineering, the Yogyakarta StateUniversity. Group A2 was selected as the experimental group, consisting of regularS1 students, and Group B1 as the control group, consisting of regular D3 students.The group members were non-randomly selected. The data were analyzed usingthe t-test. The result showed that the tobserved (17.717) was higher than the ttable(2.038) at p .05, indicating that there was a significant difference between the twogroups. The students in the experimental group attained a higher mean score thanthose in the control group. In other words, in Technical Drawing, the studentstaught by the programmed instruction model attained higher achievement thanthose taught by the conventional teaching method.Keywords: programmed instruction, Technical Drawing